Clostridioides (Clostridium) difficile–associated disease, epiploic foramen entrapment, and gastric rupture in a Thoroughbred racehorse: case report and literature review. (September 2022) - Asin, Javier; Nyaoke, Akinyi C.; Samol, Monika A.; Arthur, Rick M.; Uzal, Francisco A.
Epiploic foramen entrapment (EFE) is a common cause of small intestinal colic in horses and may lead to intestinal strangulation. Strangulating intestinal obstruction impairs the gastrointestinal outflow and can lead to secondary gastric rupture and endotoxemia. Clostridioides difficile can cause enterotyphlocolitis with colic in horses of all ages, and the process is commonly referred to as C. difficile –associated disease (CDAD). Here we report the results of the postmortem examination of a 7-y-old Thoroughbred racehorse with concurrent CDAD, EFE, and gastric rupture that was euthanized following a history of colic over several days. A segment of distal jejunum and proximal ileum had passed through the epiploic foramen, and the intestinal wall was thickened and dark-red. The remaining small intestinal loops were distended and filled with blood-tinged contents. Peritonitis had resulted from escape of gastric contents into the abdominal cavity through a tear in the major curvature of the stomach. Histologically, the incarcerated segment had acute transmural hemorrhage with congestion and mucosal necrosis; neutrophilic infiltrates with fibrin thrombi were in the mucosa of the non-incarcerated small intestinal segments. C. difficile toxins were detected in the small intestinal contents, and C. difficile was isolated from the small intestine, colon, and cecum.